Workforce Diversity and Its Impact on Organizational Success - Pokhrel, Lal Mani (Academia Research Journal, 2023)
This study examines how employee performance in Nepalese commercial banks serves as a proxy for organizational success to determine the benefits of workforce diversity. The study employed a descriptive and causal comparative research methodology to examine the employees of Bank of Kathmandu Ltd., established in Banke and Bardiya District, in order to determine the relationship between dependent factors, such as employee performance, and independent variables (i.e. age diversity, gender diversity, ethnic diversity, and level of education). The study is based on first-hand information. The descriptive design aids in determining the employees’ basic backgrounds, and the casual comparative research design aids in determining the impact and connections between each independent variable and dependent variable. The research reveals that all independent variables—including age, gender, ethnicity, and educational attainment—have a statistically significant positive connection with the dependent variable (i.e. organization effectiveness). There are increased chances of establishing organizational success there as each group’s diversity grows, and vice versa. Similar to how all independent variables have an effect on dependent variables, such as organization effectiveness, are age diversity, gender diversity, ethnic diversity, and degree of education. As a result, the effectiveness of the organization is influenced by each of the independent variables.